Polypropylene multilayer sheet

The polypropylene multilayer sheet with specific filler-resin ratios and layer configurations addresses rigidity and peelability issues, enhancing application versatility and recyclability through stable easy peelability.

JP2024176754APending Publication Date: 2024-12-19SUNALLOMER LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023095535
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-09
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing polypropylene multilayer sheets lack sufficient rigidity and stable easy peelability, making them limited in application and difficult to recycle effectively.

Method used

A polypropylene multilayer sheet design featuring alternating biaxially oriented layers with specific ratios of polypropylene resin and granular inorganic filler, where one layer contains a higher proportion of filler, facilitating easy peelability through material destruction at the filler-resin interface.

Benefits of technology

The design achieves high rigidity and stable easy peelability, enabling broader applications and improved recyclability by allowing easy separation of layers without damage to the underlying structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024176754000001_ABST
    Figure 2024176754000001_ABST
Patent Text Reader

Abstract

To provide a PP multilayer sheet with high rigidity and easy peelability.SOLUTION: The present invention provides a PP multilayer sheet with a thickness of 0.1 to 5 mm, including alternating layers in which biaxially oriented PP layers F (melting point TmF) and biaxially oriented PP layers N (melting point TmN) are alternately laminated, with TmF≥TmN, where the layers F are formed of a resin composition containing a PP resin (A) and an inorganic filler (B), with (B) / [(A)+(B)] (=X) of more than 0 wt.% to 60 wt.%. The layers N are formed of a resin composition containing a PP resin (a) and, as an optional component, (B), with (B) / [(a)+(B)] of 0 to 2 wt.%. Following conditions are fulfilled: at least one of the layers F is a layer FE with (B) being a granular inorganic filler and (I) X of 3 wt.% or more and less than 15 wt.% or (II) X of 15 to 35 wt.% and r / R≥5% where r denotes the shortest distance from a surface of the multilayer sheet to the layer FE and R denotes the total thickness of the multilayer sheet.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polypropylene multilayer sheet. [Background technology]

[0002] Stretched polypropylene films are used in fields that require high heat resistance as well as excellent transparency and mechanical properties, and various techniques for further improving these properties have been studied. For example, Patent Document 1 discloses that a sheet with an excellent balance of rigidity, transparency, heat resistance, uniform stretchability, low-temperature impact resistance, and thermoformability has been obtained from a polypropylene composition having a specific range of molecular weight distribution and a specific range of comonomer and crystal nucleating agent content. Patent Document 2 discloses a sheet made of a polymer nano-oriented crystalline material that is crystallized by cooling in a polymer oriented melt state and contains polymer nano-oriented crystalline materials with a crystal size of nanometer order and highly oriented polymer chains as the main component.

[0003] These sheets are thin and therefore have limited uses, and it is expected that their uses will expand if their thickness can be increased. In this regard, Patent Document 3 discloses the production of a multi-layer sheet having a thickness of 0.5 to 5 mm and excellent transparency and mechanical properties in addition to high heat resistance, by alternately laminating biaxially oriented polypropylene films having different melting points.

[0004] Incidentally, in order to improve the design, it is common to apply paint or decorative film to plastics, including multilayer sheets. However, when recycling the plastic molded body, it is necessary to remove the paint film and film. For example, Patent Document 4 proposes a method of cutting a resin molded body on which a paint film is formed on the surface, mixing and stirring them with metal spheres and water to peel off the paint film. In addition, Patent Document 5 proposes a method of forcibly peeling off a paint film from a plastic molded body using a high-pressure jet of water or the like. In addition, Patent Document 6 discloses a laminated film with easy peeling properties that utilizes interfacial peeling between a filler-filled layer and another layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-095698 A [Patent Document 2] JP 2012-096526 A [Patent Document 3] International Publication No. 2020 / 075755 [Patent Document 4] JP 2007-237590 A [Patent Document 5] Japanese Patent Application Publication No. 5-269743 [Patent Document 6] JP 2008-87181 A Summary of the Invention [Problem to be solved by the invention]

[0006] The multilayer sheet described in Patent Document 3 has excellent rigidity, but the inventors came up with the idea that if the rigidity of the multilayer sheet could be further increased, the applications of polypropylene could be further expanded. Furthermore, in the method described in Patent Document 4, the molded body is cut and water and a metal body are mixed and stirred, so it is difficult to separate the resin from the coating film and to remove the metal particles. In Patent Document 5, high-pressure fluid is also used, so separation and collection are difficult. Easy peelability can be achieved in two ways: by utilizing interfacial peeling as in Patent Document 6, or by utilizing material destruction of the layer itself. Interfacial peeling as in Patent Document 6 does not provide stable peel strength, and the coating film or decorative surface of the molded body may peel off during use, making it unusable. Material destruction provides a stable peel strength, so that users are more satisfied. Conventionally, an easy peel layer composed of a polymer having a sea-island structure is known as an easy peel layer that causes material destruction. In view of such circumstances, the present invention aims to provide a polypropylene multilayer sheet that has high rigidity and easy peelability. [Means for solving the problem]

[0007] The inventors have found that the above problems can be solved by using a stretched sheet or the like containing a polypropylene resin and a particulate inorganic filler. That is, the above problems are solved by the present invention described below. Aspect 1 A polypropylene multi-layer sheet having a thickness of 0.1 to 5 mm, The laminate has alternating layers in which a biaxially oriented polypropylene layer F having a melting point TmF and a biaxially oriented polypropylene layer N having a melting point TmN are alternately laminated, TmF ≧ TmN, the layer F is formed from a resin composition containing a polypropylene resin as a component (A) and an inorganic filler as a component (B), and the weight ratio of the component (B) / [component (A)+component (B)] is more than 0 to 60% by weight, the layer N is formed from a resin composition containing a polypropylene-based resin as component (a) and the component (B), and the weight ratio of component (B) / [component (a)+component (B)] is 0 to 2% by weight; Meet any of the following requirements: (I) At least one of the layers F is a layer FE in which the component (B) is a particulate inorganic filler and the weight ratio of component (B) / [component (A)+component (B)] is 3% by weight or more and less than 15% by weight. (II) At least one of the layers F is a layer FE in which the component (B) is a granular inorganic filler and the weight ratio of component (B) / [component (A)+component (B)] is 15 to 35% by weight, and r / R≧5% is satisfied, where r is the shortest distance from the surface of the multilayer sheet in the thickness direction to the interface between the layer FE and another layer and R is the total thickness of the multilayer sheet. Polypropylene multi-layer sheet. Aspect 2 The component (A) is a polypropylene-based resin composed of a component (A1) and an optional component (A2), The component (A1) is 100 to 50% by weight of a propylene (co)polymer containing 0 to 10% by weight of a comonomer-derived unit selected from C2 to C10 α-olefins (excluding C3 α-olefins), Component (A2) is 0 to 50% by weight of an ethylene-α-olefin copolymer containing more than 10% by weight and not more than 90% by weight of ethylene-derived units; The MFR of component (A) (230°C, load 2.16 kg) is 1 to 20 g / 10 min. 2. The polypropylene multi-layer sheet according to embodiment 1. Aspect 3 3. The polypropylene multi-layer sheet of any one of the preceding claims, further comprising a top layer over the alternating layers. Aspect 4 A polypropylene multi-layer sheet according to any one of aspects 1 to 3, wherein the particulate inorganic filler is calcium carbonate. Aspect 5 In the above (I), 30%≧r / R≧0.6%, or In the above (II), 30% ≧ r / R ≧ 5%; The polypropylene multilayer sheet according to any one of embodiments 1 to 4. Aspect 6 A polypropylene multilayer sheet according to any one of aspects 1 to 5, wherein the layer FE has a thickness of 10 to 1000 μm. Aspect 7 A method for producing the polypropylene multilayer sheet according to any one of aspects 1 to 6, comprising the steps of: a layer F having a melting point TmF; A step 1 of preparing a precursor in which a layer N having a melting point TmN and a layer F are laminated such that the layers F are not adjacent to each other; a step 2 of contacting an outermost layer of the precursor with a heating body to heat-seal the layers of the sheet; TmF ≧ TmN; Manufacturing method. Aspect 8 The melting point of the outermost layer F is defined as TmF out When the temperature T of the heater satisfies the following condition: TmF out -T≧4(℃) (The melting point is measured using a DSC at a temperature rise rate of 10°C / min from 30°C to 230°C.) The method of production according to embodiment 7. Aspect 9 The method of any one of claims 7 to 8, further comprising, after step 2, providing a top layer. Aspect 10 A molded article obtained by molding the polypropylene multilayer sheet according to any one of the first to sixth aspects. Aspect 11 11. The molded article according to embodiment 10, which is an automobile part. Aspect 12 A polypropylene multilayer sheet produced by the method according to any one of aspects 7 to 9. Aspect 13 The layer FE is used as an easy-peel layer. A method for peeling at least one layer from the polypropylene multilayer sheet according to any one of aspects 1 to 6 or 12, or the molded article according to aspect 10 or 11. Effect of the Invention

[0008] The present invention can provide a polypropylene multi-layer sheet having high rigidity and easy peelability. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a conceptual diagram showing the peeling state of a multilayer sheet having an easy-peel layer. [Diagram 2] FIG. 1 is a diagram illustrating an outline of a polypropylene multilayer sheet. [Diagram 3] FIG. 2 is a diagram illustrating one embodiment of a method for producing a polypropylene multilayer sheet. [Figure 4] FIG. 2 is a diagram illustrating another embodiment of the method for producing a polypropylene multilayer sheet. [Diagram 5] 1 is a micrograph showing the peeling state of a multilayer sheet obtained in an example. [Figure 6] FIG. 2 is a schematic diagram showing the peeling state of the multilayer sheet obtained in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In this disclosure, "X to Y" includes the end values, i.e., X and Y. Sheet and film are used synonymously, but in particular, a film-like member having a thickness of 150 μm or more may be called a sheet, and a film-like member having a thickness of less than 150 μm may be called a film. In addition, sheets and films may be collectively called "sheet-like members."

[0011] 1. Polypropylene multi-layer sheet (1) Thickness In one embodiment, the polypropylene multilayer sheet (hereinafter also simply referred to as "multilayer sheet") has a thickness of 0.1 to 5 mm. If the sheet is too thin, the easy peel property decreases, which may make recycling difficult. Furthermore, if the sheet is too thick, it may be difficult to manufacture. From this viewpoint, the lower limit of the thickness is preferably 0.5 mm or more, more preferably 1.0 mm or more. The upper limit of the thickness is preferably 5.0 mm or less, more preferably 4.0 mm or less, and even more preferably 3.5 mm or less. The thickness of the multilayer sheet is appropriately adjusted depending on the application.

[0012] (2)Multilayer structure The multilayer sheet has alternating layers in which biaxially oriented polypropylene layers F and biaxially oriented polypropylene layers N are laminated alternately. In one embodiment, the multilayer sheet is made of the alternating layers, and in another embodiment, the multilayer sheet has the alternating layers and another layer (e.g., a top layer). The biaxially oriented polypropylene layer F and the biaxially oriented polypropylene layer N are different layers and are not the same. For example, the two layers differ in terms of melting point, amount of inorganic filler, type of polymer, etc.

[0013] Hereinafter, the biaxially oriented polypropylene layer F is also referred to as the "filler layer F" for convenience, and the biaxially oriented polypropylene layer N is also referred to as the "neat layer N". Since each layer is fused, the multilayer sheet is an integrated sheet. Whether each layer of the sheet is fused and integrated can be confirmed by cross-sectional observation using a polarizing microscope, as described in International Publication No. 2020 / 075755.

[0014] The multilayer sheet satisfies either the following requirement (I) or (II). (I) At least one of the layers F is a layer FE in which the component (B) is a particulate inorganic filler and the weight ratio of component (B) / [component (A)+component (B)] is 3% by weight or more and less than 15% by weight. (II) At least one of the layers F is a layer FE in which the component (B) is a granular inorganic filler and the weight ratio of component (B) / [component (A)+component (B)] is 15 to 35% by weight, and r / R≧5% is satisfied, where r is the shortest distance from a surface layer of the multilayer sheet in the thickness direction to an interface between the layer FE and another layer and R is the total thickness of the multilayer sheet.

[0015] The layer FE is a layer that can exhibit easy peel properties. Unless otherwise specified, the "filler layer F" includes the layer FE, and further includes a filler layer that does not fall under the layer FE. The reason why the layer FE exhibits easy peel properties is not limited, but is presumed to be as follows. The bond strength at the interface between the particulate inorganic filler, which is the component (B), and the component (A) is lower than the breaking strength of the component (A) itself and lower than the bond strength at the interface between each layer, because it is a bond between an organic substance and an inorganic substance. Therefore, cracks occur at the interface between the component (B) and the component (A) in the stretching direction during stretching. Therefore, when an external force is applied to peel off a layer present on the layer FE, cracks occur preferentially starting from the cracks at the interface between the component (B) and the component (A) of the layer FE. The cracks propagate one after another to the component (B) that is aligned and dispersed. As a result, it is thought that easy peel properties are exhibited. However, if the amount of the particulate inorganic filler is excessive, the layer becomes brittle, and if the amount is too small, sufficient easy peel properties are not exhibited. Therefore, the easy peel property is affected by the content of the particulate inorganic filler.

[0016] [Aspect (I)] In this embodiment, at least one of the filler layers F is composed of a layer FE in which the component (B) is a particulate inorganic filler and the weight ratio of the component (B) / [component (A)+component (B)] is 3% by weight or more and less than 15% by weight. In this embodiment, the upper limit of the weight ratio of the component (B) / [component (A)+component (B)] (hereinafter also referred to as the "amount of the component (B)") is less than 15% by weight, and preferably 13% by weight or less. The lower limit is preferably 5% by weight or more. In this embodiment, the position of the layer FE in the multilayer sheet is not limited because the easy peel property is stably expressed. The position of the filler layer FE is defined by r / R. r is the shortest distance from the surface of the multilayer sheet in the thickness direction to the interface between the layer FE and another layer (see FIG. 1). There are two surfaces of the multilayer sheet, but here, it is defined as the surface that has the smallest r. R is the total thickness of the multilayer sheet. It is preferable that 30%≧r / R≧0.6%.

[0017] [Aspect (II)] In this embodiment, at least one of the layers F is a layer FE in which the component (B) is a particulate inorganic filler and the weight ratio of the component (B) / [component (A)+component (B)] is 15-35% by weight. In this embodiment, the amount of the component (B) in the layer FE is relatively large, so that the position (r / R) of the layer FE in the multilayer sheet needs to be 5% or more in order to exhibit stable easy peel properties. The lower limit of r / R is not limited, but is preferably 10% or more. The upper limit of r / R is not limited, but is preferably 30% or less. The upper limit of the amount of the component (B) is preferably 30% or less by weight, more preferably 25% or less by weight.

[0018] FIG. 1 is a schematic diagram for explaining the state of peeling of a multilayer sheet (including embodiments (I) and (II)). In the figure, 10 is a layer FE, and the easy peel is manifested by the material destruction of the layer FE. FIG. 1 shows a multilayer sheet in which an adhesive layer 15 and a top layer 20 are laminated on the layer FE10, and another layer 30 is laminated under the layer FE10. When the top layer 20 is peeled off, the material destruction occurs in the layer FE10 by the above action. As a result, the top layer 20 can be easily removed. The layer FE may be uniaxially or multiaxially stretched. Hereinafter, the layer that exhibits the easy peel property during peeling of the "layer FE" is referred to as the "easy peel layer". Therefore, in the embodiment of FIG. 1, the layer FE10 is the easy peel layer.

[0019] As described later, the filler layer F in the multilayer sheet is derived from the biaxially oriented polypropylene sheet-like member for that layer, and the neat layer N is derived from the biaxially oriented polypropylene sheet-like member for that layer. Each layer may be independently composed of the sheet-like member. This embodiment is shown in FIG. 2(A). In the figure, 1' is a precursor described later, 20 is a top layer, F is a filler layer F, FE is a layer FE, N is a neat layer N, and 1 is a multilayer sheet. The layers of the precursor 1' are fused to each other to form the multilayer sheet 1. In this embodiment, the neat layer N between the top layer 20 and the layer FE also functions as an adhesive layer. In another embodiment, an adhesive layer may be provided between the top layer 20 and the layer FE using a known adhesive. Alternatively, an adhesive layer may not be provided. In this embodiment, since there is only one layer FE, the easy peel is manifested in the layer FE. That is, in this embodiment, the layer FE is an easy peel layer.

[0020] At least a part of all layers may be composed of a coextrusion layer in which a filler layer F and a neat layer N obtained by coextrusion are alternately laminated. This embodiment is shown in Fig. 2(B). In the figure, C indicates a coextrusion layer, and for example, C[N / F] is a coextrusion layer having two layers, a filler layer F and a neat layer N. A multilayer sheet 1 is formed from a precursor 1' containing the sheet-like members C'[N / FE / N], C'[N / F], and C'[N / F / N].

[0021] The total number of layers in the alternating layers is preferably 3 to 100. When the total number of layers is within this range, excellent moldability is exhibited when the multilayer sheet is molded into a molded product, i.e., excellent moldability is obtained. The number of layers depends on the thickness of each layer, but in one embodiment, it is preferable that there are about 6 to 100 layers in total, and more preferably about 6 to 20 layers, of filler layers F and neat layers N, each having a thickness of about 0.010 to 0.30 mm. In the embodiment of FIG. 2(B), the total number of alternating layers is 8. In the embodiment including a coextruded layer, the thickness of the coextruded layer is preferably 0.015 to 0.50 mm. The total number of layers in the coextruded layer is preferably 2 to 6, more preferably 2 to 5, even more preferably 2 to 4, and particularly preferably 2 to 3. The thickness of the coextruded layer refers to the total thickness of C (represented by t in FIG. 2(B)). In the case of FIG. 2(B), the total number of coextruded layers is 4.

[0022] Regarding the ratio DF / DN of the total thickness (total thickness) DF of the filler layers F in the alternating layers to the total thickness (total thickness) DN of the neat layers N, if the value is too small, the rigidity of the multilayer sheet becomes insufficient, and if the value is too large, the fusion property between the layers of the multilayer sheet becomes insufficient. From the viewpoint of the balance between fusion property and rigidity, the ratio is preferably 1 to 30, more preferably 1 to 25, and even more preferably 2 to 15. The thicknesses of the layers may be the same or different. The thicknesses of the layers are appropriately adjusted so that the ratio falls within the above range. The thickness of one layer of the filler layers F is preferably 10 μm to 300 μm. The thickness of one layer of the neat layers N is preferably 2 μm to 200 μm.

[0023] The melting point TmF of the filler layer F and the melting point TmN of the neat layer N satisfy the relationship TmF≧TmN, preferably TmF>TmN. TmF-TmN is not limited, but is preferably 1°C or more, 5°C or more, 8°C or more, 10°C or more, or 25°C or more. The difference in melting points improves the adhesion between the layers. Furthermore, TmF-TmN is preferably 60°C or less, or 30°C or less. If these melting points are too low, the rigidity and heat resistance of the multilayer sheet become insufficient. From this viewpoint, TmF is preferably 160°C or more, more preferably 165°C or more, and TmN is preferably 100°C or more, more preferably 120°C or more, and even more preferably 130°C or more. These melting points are obtained by measuring using DSC at a heating rate of 10°C / min from 30°C to 230°C.

[0024] (3) Mechanical properties, heat resistance The multilayer sheet and molded articles such as containers obtained from the multilayer sheet have excellent mechanical properties. For example, the sheet and molded article have a tensile modulus of elasticity (JIS K7161-2) of preferably 2,000 MPa or more, more preferably 3,500 MPa or more as rigidity. The sheet and molded article also have a flexural modulus of elasticity (at 23°C, by dynamic viscoelastic analysis) of preferably 2,500 MPa or more, more preferably 3,500 MPa or more as rigidity. Alternatively, the sheet and molded article have a flexural modulus of elasticity (at 100°C, by dynamic viscoelastic analysis) of preferably 500 MPa or more, more preferably 1,000 MPa or more as rigidity at high temperature. Molded articles having such rigidity have excellent buckling resistance. The multilayer sheet also has excellent cold impact resistance. For example, the multilayer sheet and molded article preferably have a surface impact strength of 2J or more (-30°C, JIS K7211-2). Furthermore, the multilayer sheet has excellent dimensional stability. For example, the multilayer sheet and molded article preferably have a linear expansion coefficient (JIS K7197) of less than 50 pmm / K. If the linear expansion coefficient is within this range, gaps in the multilayer sheet are not noticeable and the appearance is excellent.

[0025] Containers obtained from the multilayer sheet have excellent heat resistance and can be used at a wide range of temperatures. In particular, the heat resistance temperature of the container in the buckling test is preferably 120°C or higher, more preferably 130°C or higher, even more preferably 140°C or higher, and particularly preferably 150°C or higher. Containers having a heat resistance temperature in this range in the buckling test have excellent microwave oven applicability. The buckling test is carried out by the following steps. 1) Place the container with the opening facing down on a heat-resistant plate such as a metal plate, and heat it in an oven with no load for 1 hour. 2) After opening the oven door, quickly place a load (640 g) on ​​the container and remove it after 10 seconds. 3) Remove the plate and container from the oven and visually check for buckling of the container. 4) The temperature at which the container begins to buckle is the heat resistance temperature.

[0026] (4) Surface A functional group can be added to the surface of the multilayer sheet. The functional group is preferably an oxygen-containing functional group. Examples of the oxygen-containing functional group include a carboxyl group, a carboxylate group, an acid anhydride group, a hydroxyl group, an aldehyde group, and an epoxy group. These functional groups improve the adhesion between the multilayer sheet and other materials. In particular, it is preferable to provide a coating film on a layer having a functional group, since the adhesion between the layer and the coating film is improved.

[0027] (5)Each layer 1) Filler layer F The filler layer F is formed from a resin composition containing the components polypropylene resin (A) and inorganic filler (B). [Polypropylene resin (component (A)) The polypropylene-based resin is a resin containing polypropylene as a main component. The polypropylene-based resin constituting the filler layer F preferably comprises 100 to 50% by weight of component (A1) and 0 to 50% by weight of optional component (A2). When component (A2) is more than 0% by weight, component (A) may be a so-called heterophase copolymer (HECO) obtained by polymerizing component (A1) and polymerizing component (A2) in the presence of said component, or may be a blend of components (A1) and (A2) prepared by separately polymerizing them. From the viewpoint of obtaining component (A) in fewer production steps, component (A) is preferably HECO. The polypropylene-based resin is different from so-called modified polypropylene.

[0028] Component (A1) is a propylene (co)polymer containing 0-10% by weight of a comonomer-derived unit selected from C2-C10 α-olefins (excluding C3 α-olefins). The comonomer selected from C2-C10 α-olefins does not naturally contain a C3 α-olefin. When a comonomer is contained, ethylene is preferred from the viewpoint of economy. If the amount of the comonomer-derived unit exceeds the upper limit, the rigidity of the multilayer sheet may decrease. From this viewpoint, it is preferable that component (A1) does not contain a comonomer-derived unit, that is, it is a propylene homopolymer. Alternatively, when component (A1) contains a comonomer-derived unit, the amount is preferably more than 0% by weight and 0.5% by weight or less.

[0029] The content of component (A1) in the polypropylene resin is 50 to 100% by weight. If the content of component (A1) is low, it may be difficult to produce the polypropylene resin. Therefore, the content of component (A1) is preferably 70 to 100% by weight, more preferably 75 to 100% by weight.

[0030] The MFR (230°C, load 2.16 kg) of component (A) is preferably 0.1 to 20 g / 10 min. If the MFR exceeds the upper limit, it becomes difficult to prepare the biaxially oriented polypropylene sheet member that is the raw material of the multilayer sheet, and if it is below the lower limit, it becomes difficult to produce component (A). From this viewpoint, the lower limit of the MFR is more preferably 1 g / 10 min or more, and even more preferably 2 g / 10 min or more, and the upper limit is more preferably 15 g / 10 min or less, and even more preferably 10 g / 10 min or less. The MFR is measured according to JIS K7210-1 and based on JIS K6921-2 under conditions of a temperature of 230°C and a load of 2.16 kg.

[0031] The optional component (A2) is an ethylene-α-olefin copolymer containing more than 10% by weight and not more than 90% by weight of ethylene-derived units. If the ethylene-derived units are less than the lower limit or exceed the upper limit, cold impact resistance decreases. From this viewpoint, the content of the ethylene-derived units is preferably 15 to 85% by weight, more preferably 20 to 80% by weight. The α-olefin is not limited as long as it is other than ethylene, but is preferably propylene, 1-butene, 1-hexene, or 1-octene, more preferably propylene, 1-butene, and even more preferably propylene.

[0032] The content of component (A2) in the polypropylene resin is 0 to 50% by weight. If the content of component (A2) is too high, it may be difficult to produce the polypropylene resin. Therefore, the content of component (A2) is preferably 0 to 30% by weight, more preferably 0 to 25% by weight.

[0033] In addition, when the content of component (A2) in component (A) is 0% by weight (component (A) is only component (A1)), component (A) may be a homopolymer of propylene (HOMO) containing no comonomer-derived units, or a random copolymer of propylene (RACO) containing more than 0 to 10% by weight of comonomer-derived units selected from C2 to C10 α-olefins (excluding C3 α-olefins). In one embodiment, the amount of the comonomer-derived units is about 0.2 to 1% by weight.

[0034] The total ethylene content of component (A) and the ethylene-derived unit content of component (A1) are measured by known methods, but a preferred measurement method will be described below. The copolymer sample dissolved in a mixed solvent containing 1,2,4-trichlorobenzene and deuterated benzene was analyzed by a Bruker AVANCE III HD400 ( 13 The conditions were: measurement temperature 120°C, flip angle 45°, pulse interval 7 seconds, sample rotation speed 20Hz, and cumulative number 6000. 13 A C-NMR spectrum is obtained. The mixed solvent is preferably 1,2,4-trichlorobenzene / deuterated benzene / hexamethyldisiloxane=30 / 10 / 1 (volume ratio). Using the spectrum obtained above, the total ethylene content (wt%) of component (A) is determined by the method described in Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 15, 1150-1152 (1982). When component (A1) is used as a sample for measurement, the total ethylene content (wt%) obtained by the above method is the ethylene unit content (wt%) of component (A1). When component (A1) contains units derived from a comonomer other than ethylene, the content of the comonomer units can be determined in the same manner as the content of the ethylene-derived units.

[0035] The ethylene unit content in component (A2) is also measured by a known method, but a preferred measurement method will be described below. The ethylene unit content (wt%) of component (A2) is calculated in the same manner as for the total ethylene amount, except that the integrated intensity T'ββ calculated by the following formula is used instead of the integrated intensity Tββ calculated when measuring the total ethylene amount of component (A) by the method described in the above document. T'ββ=0.98×Sαγ×A' / (1-0.98×A') Here, A'=Sαγ / (Sαγ+Sαδ), and Sαγ and Sαδ described in the above literature It is calculated as follows.

[0036] In component (A), which consists of components (A1) and (A2), when component (A1) contains ethylene units, the content of ethylene-derived units in component (A2) can be calculated by the following formula, when the weight ratio (component (A2) / [component (A1)+component (A2)]) is clear from the polymerization conditions. Content of ethylene-derived units in component (A2) (unit: weight%)= [Total ethylene content of component (A) - Ethylene-derived unit content of component (A1) x Content of component (A1) in component (A)] / (Content of component (A2) in component (A))

[0037] The weight ratio of component (A2) / [component (A1)+component (A2)] is calculated by the following formula. Component (A2) / [Component (A1)+Component (A2)](unit: weight %)=total ethylene content of component (A) / (ethylene unit content in component (A2) / 100)

[0038] [Inorganic filler (component (B))] The inorganic filler is added mainly for the purpose of improving the rigidity of the material. As described above, the layer FE contains a granular inorganic filler. The layer F other than the layer FE preferably contains a granular inorganic filler, but may contain a non-granular inorganic filler within a range that does not impair the above-mentioned effect. Examples of the granular inorganic filler include calcium carbonate and silica, and calcium carbonate is preferred. The volume average particle diameter of the inorganic filler is preferably 1 to 10 μm, more preferably 2 to 7 μm. The volume average particle diameter can be measured as a 50% diameter in a volume-based cumulative fraction by a laser diffraction method (based on JIS R1629).

[0039] Examples of inorganic fillers other than granular inorganic fillers include the following. Powdered fillers such as calcium silicate, aluminum silicate, silicic acid, or synthetic silicic acid or silicates such as silicic anhydride; plate-like fillers such as talc, kaolinite, clay, or mica; whisker-like fillers such as basic magnesium sulfate whiskers, calcium titanate whiskers, aluminum borate whiskers, sepiolite, PMF (Processed Mineral Filler), xonotlite, potassium titanate, or ellestadite; balloon-like fillers such as glass balloons or fly ash balloons; and fibrous fillers such as glass fiber.

[0040] The inorganic filler may be used alone or in combination of two or more kinds. In order to improve the dispersibility of these fillers, the inorganic fillers may be subjected to a surface treatment as necessary.

[0041] [Weight ratio of components (A) and (B)] The weight ratios of components (A) and (B) in layer F are as follows: Component (B) / [Component (A)+Component (B)]=>0~60% by weight If the amount of component (B) is small, the stiffness of the multilayer sheet is insufficient, and if the amount of component (B) is large, it may be difficult to manufacture the multilayer sheet. From this viewpoint, the weight ratio is preferably 3 to 50% by weight, 5 to 40% by weight, 5 to 35% by weight, or 5 to 30% by weight.

[0042] 2) Layer FE At least one of the filler layers F is a layer FE. The layer FE is composed of the above-mentioned component (A) and component (B) limited to a specific embodiment. The components will be described below.

[0043] [Component (A) for layer FE: Polypropylene resin] The polypropylene-based resin constituting the layer FE sheet preferably comprises 100 to 50% by weight of component (A1) and 0 to 50% by weight of optional component (A2). When component (A2) is more than 0% by weight, component (A) may be a so-called heterophase copolymer (HECO) obtained by polymerizing component (A1) and polymerizing component (A2) in the presence of said component, or may be a blend of components (A1) and (A2) prepared by separately polymerizing them. From the viewpoint of obtaining component (A) in fewer production steps, component (A) is preferably HECO.

[0044] Component (A1) is a propylene (co)polymer containing 0-10% by weight of a comonomer-derived unit selected from C2-C10 α-olefins (excluding C3 α-olefins). The comonomer selected from C2-C10 α-olefins does not naturally contain a C3 α-olefin. When a comonomer is contained, ethylene is preferred from the viewpoint of economy. If the amount of the comonomer-derived unit exceeds the upper limit, the rigidity of the sheet may decrease, or the production of a polypropylene-based resin may become difficult. From this viewpoint, component (A1) preferably contains 0-1% by weight of a comonomer-derived unit, and more preferably does not contain a comonomer-derived unit, i.e., is a propylene homopolymer. Alternatively, when component (A1) contains a comonomer-derived unit, the amount is preferably more than 0% by weight and 0.5% by weight or less.

[0045] In the polypropylene resin, the content of component (A1) is 50 to 100% by weight. If the content of component (A1) is small, the rigidity of the sheet may decrease, or the production of the polypropylene resin may become difficult. Therefore, the content of component (A1) is preferably 60 to 100% by weight. The content of component (A2) is 0 to 50% by weight, preferably 0 to 40% by weight.

[0046] The optional component (A2) is an ethylene-α-olefin copolymer containing more than 10% by weight and not more than 90% by weight of ethylene-derived units. If the ethylene-derived units are less than the lower limit or exceed the upper limit, cold impact resistance decreases. From this viewpoint, the content of the ethylene-derived units is preferably 15 to 85% by weight, more preferably 20 to 80% by weight. The α-olefin is not limited as long as it is other than ethylene, but is preferably propylene, 1-butene, 1-hexene, or 1-octene, more preferably propylene or 1-butene, and even more preferably propylene.

[0047] As described above, component (A) may be a propylene homopolymer (HOMO) or a propylene random copolymer (RACO) containing 0 to 10% by weight of a comonomer-derived unit selected from C2 to C10 α-olefins (excluding C3 α-olefins). These embodiments correspond to the case where the content of component (A1) is 100% by weight.

[0048] The MFR of component (A) (230°C, load 2.16 kg) is preferably 1 to 20 g / 10 min. If the MFR exceeds the upper limit, it becomes difficult to stably stretch the sheet for layer FE. If the MFR is below the lower limit, it becomes difficult to easily stretch the sheet for layer FE. From this viewpoint, the lower limit of the MFR is more preferably 2 g / 10 min or more, and even more preferably 3 g / 10 min or more, and the upper limit is more preferably 15 g / 10 min or less, and even more preferably 10 g / 10 min or less.

[0049] [Component for layer FE (B): inorganic filler] The component (B) for layer FE is a granular inorganic filler as described above. Examples of the granular inorganic filler include calcium carbonate or silica, with calcium carbonate being preferred. The volume average particle diameter of the inorganic filler is preferably 1 to 10 μm, more preferably 2 to 7 μm. If the volume average particle diameter is less than the lower limit, the easy peel property may be insufficient. If the volume average particle diameter exceeds the upper limit, breakage is likely to occur during stretching, making it difficult to prepare a stretched sheet-like member that is the raw material for the layer FE sheet. The volume average particle diameter can be measured as the 50% diameter in the cumulative volume fraction by a laser diffraction method (based on JIS R1629).

[0050] [Weight ratio of components (A) and (B) for layer FE] The weight ratio of components (A) and (B) in the layer FE, that is, the amount of component (B) is as described in the embodiments (I) and (II).

[0051] Thickness If the layer FE is too thin, the easy peel property is not stable, and if it is too thick, the peelability may decrease and the recyclability may also decrease. From this viewpoint, the thickness of the layer FE is preferably 10 to 1000 μm. The lower limit is preferably 15 μm or more, more preferably 20 μm or more. The upper limit is preferably 300 μm or less, more preferably 200 μm or less.

[0052] 3) NEETs The neat layer N is formed from a resin composition containing a polypropylene resin as component (a) and optionally the component (B). The component (a) is selected so as to satisfy the relationship between TmF and TmN, and is preferably selected from propylene homopolymers (HOMO); propylene random copolymers (RACO) containing at least one comonomer selected from 5% by weight or less of C2 to C10-α olefins (excluding C3-α olefins); or a combination of these HOMO and RACO. If the amount of the comonomer-derived units is too small, the fusion with the layer F may be insufficient, and if it is too large, the rigidity of the multilayer sheet may decrease. From this viewpoint, the amount of the comonomer-derived units is preferably more than 0% by weight and 4.5% by weight or less. As the comonomer, ethylene (C2-α olefin) is preferable.

[0053] The MFR (230°C, load 2.16 kg) of the polymer or resin composition constituting the neat layer N is preferably 1 to 20 g / 10 min, more preferably 2 to 15 g / 10 min, and even more preferably 3 to 10 g / 10 min. If the MFR is too small, it becomes difficult to produce the polypropylene resin as the raw material, and if it is too large, breakage occurs during biaxial stretching, making it impossible to stably produce the multilayer sheet.

[0054] [Weight ratio of components (a) and (B)] The weight ratio of components (a) and (B) in the neat layer N is preferably as follows: Component (B) / [Component (a)+Component (B)]=0~2% by weight In particular, when the production of a multilayer sheet includes a step of preparing a raw sheet by coextrusion, if the amount of component (B) in raw sheet N'' (corresponding to neat layer N of the multilayer sheet) is large, it becomes difficult to stretch the raw sheet, so the weight ratio is preferably 1 wt % or less. The weight ratio is more preferably 0.5 wt % or less, more preferably 0 wt %. The weight ratio in neat layer N is smaller than the weight ratio in filler layer F.

[0055] (6) Nucleating agent Layer F or Layer N may be composed of a resin composition containing a nucleating agent, or may be composed of a resin composition or polymer not containing a nucleating agent. A nucleating agent is an additive used to increase the crystalline component in a resin to enhance rigidity. Known additives can be used as such additives. From an economical viewpoint, the amount of the nucleating agent is preferably 1 part by weight or less per 100 parts by weight of the polymer.

[0056] (7) Other additives The resin composition constituting the filler layer F and the neat layer N may contain conventional additives that are usually used in polyolefins, such as antioxidants, chlorine absorbers, heat stabilizers, light stabilizers, ultraviolet absorbers, internal lubricants, external lubricants, antiblocking agents, antistatic agents, antifogging agents, flame retardants, dispersants, copper inhibitors, neutralizing agents, plasticizers, crosslinking agents, peroxides, oil extenders, organic pigments, or inorganic pigments, within a range that does not impair the desired effects. The amount of each additive added may be a known amount. In addition, the resin composition may contain synthetic resins other than the polypropylene-based resins (e.g., modified polypropylene, etc.) or synthetic rubbers within a range that does not impair the effects of the present invention. The synthetic resins or synthetic rubbers may be one type or two or more types.

[0057] (8) Precursor As described later, the multilayer sheet is preferably produced through a precursor in which the filler layer F and the neat layer N are laminated so that the layers F are not adjacent to each other and have one or more interlayers that are not fused. The precursor is made into a multilayer sheet by fusing the interlayers. The precursor is also directly made into a molded body by being shaped into a desired shape and fusing the interlayers. A part of the layers constituting the precursor may be composed of the coextruded layer described above. Thus, in one embodiment, all the interlayers of the precursor are peeled off, and in another embodiment, one or more interlayers are fused and one or more interlayers are peeled off. The interlayer fusion in another embodiment is due to coextrusion and not due to the heat-pressure bonding described later.

[0058] 2.Applications The multilayer sheet has a high degree of orientation in the in-plane direction and a specific high-order structure, and the degree of orientation has a small dependency on the thickness direction, so that it is lightweight yet has excellent mechanical properties. Furthermore, the multilayer sheet has easy peel properties and the top layer can be easily peeled off, so that it is also excellent in recyclability. Therefore, the multilayer sheet has excellent recyclability and rigidity, so it can be used as a molded body such as an automobile part, an electric and electronic part, or a housing member as a steel plate replacement. In addition, the multilayer sheet is useful as a food packaging material, a container or a lid, etc. that is thin and reduced in weight and has excellent opening properties. In addition, since the multilayer sheet has high rigidity, it is useful as miscellaneous goods, daily necessities, home appliance parts, toy parts, furniture parts, building materials, packaging parts, industrial materials, logistics materials, agricultural materials, etc. The molding of the multilayer sheet is also called secondary molding, and the molded body obtained by this is also called a secondary molded body. Examples of secondary molding include known press molding, hot plate molding, stretch molding, rolling molding, drawing molding, pressure welding molding, fusion molding, vacuum molding, pressure molding, vacuum pressure molding, and the like.

[0059] The multilayer sheet can be used as a steel plate substitute material with recyclability, so the recycling method will be explained below using automotive materials as an example.

[0060] Since the layer FE of the multilayer sheet can exhibit easy peel properties, the layers above the layer FE and the layers below the layer FE can be easily divided. The top layer provided to impart design and the like is usually composed of a resin other than polypropylene. Therefore, if the top layer can be peeled off, the remaining layers can be easily recycled. In addition, if the layer FE is disposed at a desired location in the multilayer sheet, a layer having easy peel properties can be disposed at a desired location. Thus, the present embodiment also provides a peeling method for peeling off at least one layer from the polypropylene multilayer sheet or molded body, in which the layer FE is used as an easy peel layer.

[0061] When there are multiple layers FE, the position of the layer that exhibits easy peeling during peeling can be determined by controlling the thickness of each layer, the content of inorganic filler, and the position of the layer FE in the multilayer sheet. Also, as in the case of a peeling test, the position can be determined by providing an initiation point in a specific layer. For example, if an initiation point is provided in a layer FE, the layer FE undergoes material destruction and exhibits easy peeling properties. Also, if an initiation point is provided in a layer N, the layer FE adjacent to the layer N undergoes material destruction and exhibits easy peeling properties. When layers FE exist on both sides of the layer N where the initiation point is provided, the layer FE on one side undergoes material destruction and exhibits easy peeling properties.

[0062] The peel strength is not limited, but in one embodiment, from the viewpoint of a balance between high adhesion and high releasability, it is preferably 3 to 200 N / 15 mm, more preferably 6 to 100 N / 15 mm, and further preferably 8 to 50 N / 15 mm. The peel strength is determined by a 180-degree peel test using a rectangular test piece having a width of 15 mm. In one embodiment, the distance between the grippers is 50 mm, the moving speed of the grippers is 300 mm / min, the tensile length is 100 mm, and the average value of the test force in the stable section of 50 mm during material destruction is used as the test value.

[0063] The peel strength is preferably measured by the following method. This is performed using a 180-degree peel test. The multilayer sheet is cut into strips 15 mm wide to form test pieces. The top layer and bottom layer are clamped between grips, with the distance between the grips being 50 mm. The tensile test is performed by moving the grips at a speed of 300 mm / min. The material is pulled for 100 mm or more, and the average test force in the stable zone of 50 mm during material destruction is taken as the test value for peel strength. For example, an Autocom universal testing machine manufactured by TSE Co., Ltd. can be used as the test equipment.

[0064] 3. Manufacturing method The multilayer sheet is preferably manufactured by a method including step 1 of preparing a precursor in which a filler layer F and a neat layer N are laminated so that the filler layers F are not adjacent to each other, and step 2 of contacting a heating body with the outermost layer of the precursor to heat-seal the layers of the sheet. As described above, at least one layer of the filler layer F can be a layer FE, so that at least one layer of the filler layer F in the precursor can be a layer FE. In this case, after step 2, the top layer 20 can be provided by a method such as painting. Alternatively, a multilayer sheet provided with a top layer can be manufactured at once through steps 1 and 2 using a precursor provided with a top layer 20 as the precursor. The manufacturing method of the multilayer sheet can be in accordance with the method described in PCT / JP2021 / 041525. In this specification, the contents of PCT / JP2021 / 041525 are incorporated by reference.

[0065] For the sake of brevity, the manufacturing method will be described below with reference to Figs. 3 and 4, taking as an example an embodiment in which a top layer 20 is provided by a known method after step 2. The melting point TmF of the filler layer F and the melting point TmN of the neat layer N satisfy the relationship TmF ≧ TmN, preferably TmF> TmN, and more preferably TmF-TmN ≧ 1 (°C). The difference in melting points improves the adhesion between the layers. In the figures, f, fe, and n are resin compositions that ultimately constitute the layers F, FE, and N. F", FE", and N" are unstretched sheets (raw sheets) that ultimately constitute layers F, FE, and N. F', FE', and N' are biaxially oriented sheet-like members that ultimately constitute layers F, FE, and N. 1' is the precursor, 1 is the multilayer sheet, F is the filler layer, FE is the layer FE, and N is the neat layer. Also, 2 is the unstretched sheet preparation step, 3 is the stretching step, 4 is the lamination step, and 5 is the interlayer fusion step. The melting points TmF" and TmN", the melting points TmF' and TmN' of the biaxially oriented sheet-like members, and the melting points TmF and TmN of the layers have the following relationship. TmF' = TmF = TmF” + x (°C) (i) TmN' = TmN = TmN" + y (°C) (ii) Although x and y vary depending on the stretching state and the like, they are each independently preferably 1 to 10°C, and more preferably about 2 to 7°C.

[0066] (1) Process 1 In this step, the precursor is prepared. A part of the layers constituting the precursor may be composed of the coextrusion layer described above. All layers of the precursor are not fused, or some are fused.

[0067] This step can be carried out, for example, by separately preparing a biaxially oriented polypropylene sheet member F' for the filler layer F and a biaxially oriented polypropylene sheet member N' for the neat layer N, and laminating them alternately. For example, the precursor 1' can be prepared by laminating them in the order of F' / N' / ··· / F'. Furthermore, among the biaxially oriented polypropylene sheet members F', at least one layer is a biaxially oriented polypropylene sheet member F' for an easy peel layer (hereinafter also referred to as "biaxially oriented polypropylene sheet member FE'"). The location of the biaxially oriented polypropylene sheet member FE' is adjusted so that it is finally disposed at the position described above.

[0068] One embodiment of this step is shown in Figure 3. In this embodiment, biaxially oriented polypropylene sheet members F', FE', and N' are prepared separately and laminated alternately to prepare precursor 1'. In this case, it is preferable that all layers are not fused, but one or some layers may be fused. From the viewpoint of increasing the heat resistance of the obtained sheet, it is preferable that the outermost layers are biaxially oriented polypropylene sheet member F' and biaxially oriented polypropylene sheet member FE'.

[0069] The biaxially oriented polypropylene sheet member N' can be prepared by a known method. For example, an original sheet (unoriented polypropylene sheet member N") is prepared from the raw resin composition n, and this is biaxially stretched by a known method to obtain the biaxially oriented polypropylene sheet member N'. The thickness of the original sheet is preferably more than 0.10 mm, and although there is no upper limit, from the viewpoint of ease of handling, etc., it is preferably 6 mm or less. The temperature (V) during biaxial stretching is not limited, but is preferably in the range of (TmN"-10°C) to TmN". TmN" is the melting point (°C) of the raw sheet. It can be determined by performing DSC measurement under conditions of a temperature rise rate of 10°C / min from 30°C to 230°C.

[0070] The biaxially oriented polypropylene sheet member F' can be produced in the same manner as the biaxially oriented polypropylene sheet member N', but since it contains a relatively large amount of inorganic filler, it is preferable to set the temperature V during biaxial stretching so as to satisfy the following relationship. -3≦V-TmF”≦3 TmF" is the melting point (°C) of the raw sheet. It can be determined by performing DSC measurement under conditions of a temperature rise rate of 10°C / min from 30°C to 230°C.

[0071] The thickness of the raw sheet of the biaxially oriented polypropylene sheet-like member F' is preferably more than 0.15 mm, and although there is no upper limit, it is preferably 6 mm or less from the viewpoint of ease of handling. The stretching ratio is preferably 4 to 6 times in one axis from the viewpoint of rigidity. The ratio in one axis and the ratio in the other axis may be the same or different. The two axes are preferably perpendicular to each other.

[0072] This step is preferably carried out using a coextruded sheet member having layers F and N. In this way, step 2 can be simplified. This embodiment is shown in FIG. 4. Specifically, the raw material of layer F and the raw material of layer N are coextruded to prepare a coextruded raw sheet C'' having multiple layers, which is then biaxially stretched to prepare a coextruded biaxially stretched sheet member C'. The temperature V when biaxially stretching the coextruded raw sheet C'' is preferably selected so as to satisfy the above-mentioned relationship when biaxially stretching the raw sheet of the biaxially stretched polypropylene sheet member F'. Next, the coextruded biaxially stretched sheet members C' are laminated together, or the coextruded biaxially stretched sheet member C' and the above-mentioned biaxially stretched sheet member F' or N' are laminated to prepare a precursor 1'. In this case, the total number of coextruded biaxially stretched sheet members C' in the precursor 1' is not limited, but is preferably 3 to 14. The thickness of the coextruded biaxially stretched sheet member C' is preferably 0.02 to 0.50 mm, more preferably 0.02 to 0.30 mm. The coextruded biaxially stretched sheet member C' preferably has 2 to 5 layers. When the coextruded biaxially stretched sheet member C' has three or more layers, the two outer layers are preferably layer N.

[0073] As shown in FIG. 4, a precursor is obtained from a coextruded biaxially oriented sheet member C', a biaxially oriented sheet member F', and a biaxially oriented sheet member N', and a multilayer sheet can be produced. Precursor: FE' / C'[N / F / N] / F' Multi-layer sheet: FE / N / F / N / F In this precursor, layers F' (F'E) and C' are not fused together.

[0074] Also, from the precursor shown below, the central N layers are fused together to obtain a three-layered sheet. Precursor: C'[FE / N] / C'[N / F] Multi-layer sheet: FE / N / F

[0075] Alternatively, from a precursor using a coextruded three-layer biaxially stretched sheet member, the two central N layers are fused together to form a five-layer multilayer sheet. Precursor: C'[FE / N] / C'[N / F / N] / C'[N / F] Multi-layer sheet: FE / N / F / N / F

[0076] The monolayer biaxially oriented sheet-like member and the coextruded biaxially oriented sheet-like member can each be placed in any direction, and depending on the placement, the orientation direction within the plane of the multilayer sheet can be adjusted.

[0077] (2) Process 2 In this step (FIG. 3 and FIG. 4, 5), a heating body is brought into contact with the outermost layer of the precursor 1' of the multilayer sheet to heat-seal each layer. The melting point TmF of the outermost layer F of the layers F out and the temperature T of the heater is TmF out It is preferable that the relationship of -T≧4(°C) is satisfied. By satisfying this relationship, the layers can be well fused. From this viewpoint, it is more preferable that the temperature difference is 6°C or more. There is no upper limit to the temperature difference, but from the viewpoint of the production of polypropylene, it is preferably 40°C or less, more preferably 30°C or less. T can be measured by any method, but it is preferable to measure it using a non-contact thermometer such as a radiation thermometer. TmF out corresponds to the melting point of the layer disposed on the outermost layer of Layer F. The melting point is defined as the peak temperature of the melting curve obtained by measuring by DSC under conditions of a heating rate of 10°C / min from 30°C to 230°C.

[0078] The temperature T of the heater preferably satisfies the relationship TmF≧T≧TmN, and more preferably satisfies the relationship TmF≧T≧TmN+10(°C). If T exceeds the upper limit, the laminate may melt and the mechanical properties may deteriorate. If T is less than the lower limit, the layers may not be sufficiently fused together, and the mechanical properties may deteriorate. The specific temperature of the heater is preferably about 120 to 190°C, more preferably 140 to 170°C, and even more preferably 150 to 165°C.

[0079] This step is preferably carried out continuously using a heating roll as a heating body. Specifically, the precursor of the multilayer sheet is passed between two heated rolls to fuse the layers. Two rolls are used as one set, and a heating roll consisting of two or more sets of rolls may be used as a heating body to fuse the layers. The pressure applied at this time is appropriately adjusted. The take-up speed in the roll molding is not limited, but is preferably about 0.05 to 10 m / min.

[0080] Methods other than roll molding include pressure molding and fusion molding. When heat-fusing the sheet-like member, it is preferable to apply pressure to suppress heat shrinkage and to promote orientation. The pressure is adjusted according to the fusion temperature.

[0081] (3) Formation of the top layer In this embodiment, the top layer 20 can be provided by a known method. For example, these layers can be provided by painting. The type of coating is not limited, and is not limited as long as it is one that is usually used in the painting field.

[0082] The top layer is preferably a coating film used in vehicle body painting. Examples of such coating films include epoxy coating films, urethane coating films, and polyester coating films. If necessary, a lower coating film (primer coating film), a middle coating film, or an upper coating film (clear coating film) may be provided. When the multilayer sheet is used as a sheet for applying coating (coating sheet), it is preferable that the surface to be painted has a functional group.

[0083] (4) Adhesive layer The adhesive layer can be provided by a known method. The N layer can be used as the adhesive layer. In addition, the surface of the multilayer sheet can be subjected to plasma treatment or corona treatment to impart oxygen-containing functional groups to the surface, which can be used as the adhesive layer. Alternatively, a polypropylene film having functional groups can be prepared, and a precursor can be prepared in the above step 1 so that the functional group-containing film becomes the outermost layer, thereby imparting oxygen-containing functional groups to the surface of the multilayer sheet, which can be used as the adhesive layer.

[0084] The polypropylene film having oxygen-containing functional groups can be obtained by forming a known polypropylene such as maleic anhydride-modified polypropylene or epoxy-modified polypropylene into a film. The thickness of the functional group-containing film is not limited, but is preferably less than 150 μm. The functional group-containing film may or may not be biaxially stretched. In the lamination step, the polypropylene film having functional groups and the polypropylene sheet having no functional groups may be laminated simultaneously, or a polypropylene sheet having no functional groups may be laminated in advance to produce a laminated sheet, and the polypropylene film having functional groups may be laminated on the surface of the sheet. However, the method of laminating simultaneously is preferable in consideration of workability.

[0085] (5) Other processes The production method may further include a known step of cooling the multilayer sheet obtained in the previous step, etc. The cooling method is not limited, but examples thereof include a method of cooling at room temperature, and a method of cold pressing at room temperature or at 10 to 20°C.

[0086] The multilayer sheet has good interlayer adhesion and therefore almost no discontinuity between the layers. Therefore, it can be handled as an integrated sheet. With conventional methods, it was not industrially realistic to obtain a biaxially oriented multilayer sheet having a thickness of 0.20 mm or more from the viewpoint of cost, etc., but with the present invention, it is possible to industrially produce a multilayer sheet having a thickness of 0.15 mm or more and oriented in two or more directions. EXAMPLES

[0087] 1. Preparation of Sheet-like Members [Polymer B] The solid catalyst used in the polymerization was prepared according to the method described in Example 1 of EP 674991. The solid catalyst was MgCl 2 Ti and diisobutyl phthalate as an internal donor were supported on the catalyst by the method described in the above patent publication. The solid catalyst was contacted with TEAL and dicyclopentyldimethoxysilane (DCPMS) at −5° C. for 5 minutes in amounts such that the weight ratio of TEAL to the solid catalyst was 11 and the weight ratio of TEAL / DCPMS was 3. The obtained catalyst system was suspended in liquid propylene and held at 20° C. for 5 minutes to carry out prepolymerization. The obtained prepolymer was introduced into a polymerization reactor, and then hydrogen, propylene, and ethylene were fed. Then, at a polymerization temperature of 75° C., a hydrogen concentration of 0.44 mol%, and an ethylene concentration of 1.07 mol%, the polymerization pressure was adjusted to obtain polymer B as a propylene-ethylene copolymer. Polymer B (component (A)=component (A1), hereinafter also referred to simply as “PP component”) contained 4.0% by weight of ethylene-derived units (hereinafter also referred to simply as “C2”), and had an MFR (temperature 230° C., load 2.16 kg) of 7.5 g / 10 min.

[0088] [Resin composition (b)] 0.2 parts by weight of an antioxidant (BASF B225) and 0.05 parts by weight of a neutralizer (Dannan Chemical Industry Co., Ltd. calcium stearate) were blended with 100 parts by weight of polymer B, and the mixture was mixed by stirring for 1 minute with a Henschel mixer. The mixture was melt-kneaded at a cylinder temperature of 230°C using a NVC φ50mm single-screw extruder manufactured by Nakatani Machine Co., Ltd., and the extruded strand was cooled in water and then cut with a pelletizer to obtain a pellet-shaped resin composition (b). The resin composition (b) had an MFR (temperature 230°C, load 2.16 kg) of 7.5 g / 10 min.

[0089] [Polymer C] The solid catalyst used in the polymerization was prepared by the method described in Example 1 of JP 2011-500907 A. The solid catalyst was MgCl 2The solid catalyst was supported on the catalyst by the method described in the above patent publication, with Ti and diethyl-2,3-(diisopropyl)succinate as an internal donor. The solid catalyst was contacted with triethylaluminum (TEAL) and dicyclopentyldimethoxysilane (DCPMS) in amounts such that the weight ratio of TEAL to the solid catalyst was 11 and the weight ratio of TEAL / DCPMS was 15 at 12°C for 24 minutes. The obtained catalyst system was suspended in liquid propylene and held at 20°C for 5 minutes to carry out prepolymerization. The obtained prepolymer was introduced into a polymerization reactor, and then hydrogen, propylene, and ethylene were fed. Polymer C was obtained as a propylene-ethylene copolymer by adjusting the polymerization pressure at a polymerization temperature of 80°C, a hydrogen concentration of 0.16 mol%, and an ethylene concentration of 0.08 mol%. Polymer C (PP component) contained 0.35% by weight of C2, and had an MFR (temperature 230° C., load 2.16 kg) of 4.2 g / 10 min.

[0090] [Resin composition (c)] 0.2 parts by weight of an antioxidant (BASF B225) and 0.05 parts by weight of a neutralizer (Dannan Chemical Industry Co., Ltd. calcium stearate) were blended with 100 parts by weight of polymer C, and the mixture was mixed by stirring for 1 minute with a Henschel mixer. The mixture was melt-kneaded at a cylinder temperature of 230°C using a NVC φ50mm single-screw extruder manufactured by Nakatani Machine Co., Ltd., and the extruded strand was cooled in water and then cut with a pelletizer to obtain a pellet-shaped resin composition (c). The resin composition (c) had an MFR (temperature 230°C, load 2.16 kg) of 4.2 g / 10 min.

[0091] [Polymer K] Except for changing the hydrogen concentration to 0.22 mol% and the ethylene concentration to 0.58 mol%, polymer K was obtained in the same manner as polymer B. Polymer K contained 2.2 wt% of C2 and had an MFR (temperature 230°C, load 2.16 kg) of 5.0 g / 10 min.

[0092] [Resin composition (k)] 0.2 parts by weight of an antioxidant (BASF B225) and 0.05 parts by weight of a neutralizer (Dannan Chemical Industry Co., Ltd. calcium stearate) were blended with 100 parts by weight of polymer K, and the mixture was mixed by stirring for 1 minute with a Henschel mixer. The mixture was melt-kneaded at a cylinder temperature of 230°C using a NVC φ50mm single-screw extruder manufactured by Nakatani Machine Co., Ltd., and the extruded strand was cooled in water and then cut with a pelletizer to obtain a pellet-shaped resin composition (k). The MFR (temperature 230°C, load 2.16 kg) of the resin composition (k) was 5.0 g / 10 min.

[0093] [Polymer L] MgCl 2 A solid catalyst carrying Ti and diisobutylphthalate as an internal donor thereon was prepared by the method described in lines 21 to 36 of paragraph 0032 of JP-A 2004-27218. Next, the solid catalyst was contacted with triethylaluminum (TEAL) as an organoaluminum compound and dicyclopentyldimethoxysilane (DCPMS) as an external electron donor compound at a weight ratio of 20 to the solid catalyst and a weight ratio of 10 to TEAL / DCPMS (equivalent to the molar ratio of organosilicon compound / organoaluminum of 0.05) for 24 minutes at 12° C. The obtained catalyst system was suspended in liquid propylene and maintained at 20° C. for 5 minutes to carry out prepolymerization. The obtained prepolymer was introduced into the first-stage polymerization reactor of a polymerization apparatus equipped with two-stage polymerization reactors in series, and propylene was supplied to produce a propylene homopolymer (component (A1)). Subsequently, propylene homopolymer, propylene and ethylene were supplied to the second-stage polymerization reactor to produce an ethylene-propylene copolymer (component (A2)). During the polymerization, the temperature and pressure were adjusted, and hydrogen was used as a molecular weight regulator. The polymerization temperature and the ratio of reactants in the first reactor were 80°C and 0.77 mol% for the polymerization temperature and hydrogen concentration, respectively, and in the second reactor, the polymerization temperature, hydrogen concentration, and the ratio of ethylene to the total of ethylene and propylene were 80°C, 1.61 mol%, and 0.50 mol ratio, respectively. The polymerization times in the first and second stages were adjusted so that the weight ratio component (A2) / [component (A1)+component (A2)] was 18.5 wt%. The target polymer L was obtained by the above method.

[0094] The obtained polymer L is a polymerization mixture of component (A1), which is a propylene polymer constituting the continuous phase, and component (A2), which is an ethylene-propylene copolymer constituting the rubber phase, and is the aforementioned polypropylene-based resin (A). The ethylene-derived unit content (C2) of component (A1), the weight ratio component (A2) / [component (A1)+component (A2)], the ethylene-derived unit content of component (A2), and the MFR of component (A1)+component (A2) of polymer L were 0% by weight, 18.5% by weight, 51% by weight, and 16.5 g / 10 min, respectively.

[0095] [Resin composition (l)] 0.2 parts by weight of an antioxidant (BASF B225) and 0.05 parts by weight of a neutralizer (Dannan Chemical Industry Co., Ltd. calcium stearate) were blended with 100 parts by weight of polymer L, and the mixture was mixed by stirring for 1 minute with a Henschel mixer. The mixture was melt-kneaded at a cylinder temperature of 230°C using a NVC φ50mm single-screw extruder manufactured by Nakatani Machine Co., Ltd., and the extruded strand was cooled in water and then cut with a pelletizer to obtain a pellet-shaped resin composition (l). The MFR (temperature 230°C, load 2.16 kg) of the resin composition (l) was 16.5g / 10min.

[0096] [Calcium carbonate masterbatch resin composition (m)] (MB2) 35% by weight of the resin composition (l) was mixed with 54.9% by weight of calcium carbonate (NN♯500 manufactured by Nitto Funka Kogyo Co., Ltd.), 10% by weight of acid-modified polypropylene (ER321P manufactured by Mitsubishi Chemical Corporation), and 0.1% by weight of dimyristyl thiodipropionate (Yoshinox DMTP manufactured by Yoshitomi Pharmaceutical Co., Ltd.) as an antioxidant, by stirring with a Henschel mixer for 1 minute to obtain a mixture. The mixture was then melt-kneaded (twin-screw melt-kneading) by feeding it to an extruder (TEX-30α co-rotating twin-screw extruder manufactured by Japan Steel Works, Ltd.) with a screw temperature set to 230°C. The molten mixture was then discharged from the extruder, cooled to form strands, and the strands were cut to obtain pellets of the calcium carbonate masterbatch resin composition (m). The MFR (temperature 230°C, load 2.16 kg) of the masterbatch resin composition (m) was 8.0g / 10min. The physical properties of each polymer and resin composition are summarized in the table below.

[0097] [Table 1]

[0098] [Resin compositions (n) to (q)] Resin compositions (n) to (q) were prepared by dry blending the resin composition (c) and the calcium carbonate masterbatch resin composition (m) so that the calcium carbonate content in the composition was the ratio shown in Table 2. The blend ratio of the resin composition (c):calcium carbonate masterbatch resin composition (m) in the resin compositions (n) to (q) was as follows, respectively. Resin composition (n) is 9:1 Resin composition (o) is 8:2 Resin composition (p) is 6:4 For resin composition (q), it is 4:6.

[0099] [Biaxially oriented sheet NFN-9~12] Using a 25mmφ3-type 3-layer film / sheet molding machine (manufactured by Thermo Plastics Industries Co., Ltd.), resin composition (k) / resin composition (n) to resin composition (q) / resin composition (k) were co-extruded at a molding temperature of 250°C to obtain a raw sheet (size 10cm x 10cm or more) having a thickness of 1.0mm. Using a film stretching device (KARO-IV manufactured by Bruckner), the raw sheet was simultaneously biaxially stretched (6 times x 6 times) at 165°C to obtain a co-extruded biaxially stretched sheet NFN-9 to NFN-12 having a thickness of 0.025mm. The thickness ratio was 10 / 80 / 10.

[0100] [Unstretched sheet NQN_U] Using a 25 mmφ type 3 three-layer film / sheet molding machine (manufactured by Thermo Plastics Industry Co., Ltd.), resin composition (b) / resin composition (c) / resin composition (b) was co-extruded at a molding temperature of 230°C to obtain a sheet with a thickness of 1.0 mm (size 10 cm x 10 cm or more), which was designated as unstretched sheet NQN_U.

[0101] [Unstretched sheet NQN_U-2] Using a 25 mm φ3-type 3-layer film / sheet molding machine (manufactured by Thermo Plastics Industry Co., Ltd.), resin composition (k) / resin composition (c) / resin composition (k) were co-extruded at a molding temperature of 250°C to obtain a raw sheet (size 10 cm x 10 cm or more) with a thickness of 0.3 mm, which was designated as unstretched sheet NQN_U-2.

[0102] [Unstretched sheet NQN_U-3] Using a 25 mm φ3-type 3-layer film / sheet molding machine (manufactured by Thermo Plastics Industry Co., Ltd.), resin composition (k) / resin composition (c) / resin composition (k) were co-extruded at a molding temperature of 250°C to obtain a raw sheet (size 10 cm x 10 cm or more) with a thickness of 1.0 mm, which was designated as unstretched sheet NQN_U-3.

[0103] [Biaxially oriented sheet NQN-2] The unstretched raw sheet NQN_U-3 was simultaneously biaxially stretched (6 times x 6 times) at 165°C using a film stretching device (Bruckner KARO-IV) to obtain a coextruded biaxially stretched sheet NQN-2 with a thickness of 0.025 mm. The thickness ratio was 10 / 80 / 10. The physical properties of these sheets (except for the unstretched sheets NQN_U and NQN_U-3) are shown in Table 2.

[0104] 2. Manufacturing of multi-layer sheets [Example 1] Six sheets of NFN-9 were stacked, and a polyimide tape was inserted between the third and fourth sheets from the top. A precursor was prepared by stacking NQN-2 on top of the laminate and two sheets of NQN_U on the bottom. A multilayer sheet was produced as a laminate by heat-sealing each layer of the precursor using a heater and a Shoji Co., Ltd. press molding machine heated to 160 ° C. During pressing, both sides of the precursor were sandwiched from the outside by an aluminum plate having a thickness of 3 mm and a steel plate having a thickness of 1 mm, and pressed at 4 MPa for 2 minutes. In this way, a multilayer sheet having a thickness of 2.2 mm was produced. The peeling strength of the multilayer sheet was measured by the method described below. Material destruction was observed in the layer FE located immediately below the polyimide tape, and it was confirmed that the layer functions as an easy peel layer. The results are shown in Table 3.

[0105] [Examples 2 to 5] A multilayer sheet was produced and evaluated in the same manner as in Example 1, except that the layer structure of the precursor was changed as shown in the table. As a result, material failure was observed in layer FE, and it was confirmed that the layer functions as an easy-peel layer. The results are shown in Table 3.

[0106] The layer structure is shown below. Working Example 1 NQN-2 / NFN-9×3 / / NFN-9×3 / NQN_U / NQN_U 2 NQN-2 / NFN-10×3 / / NFN-10×3 / NQN_U / NQN_U 3 NQN_U-2 / NFN-11×2 / / NFN-11×2 / NQN_U-2×7 4 NQN_U-2 / NFN-12×2 / / NFN-12×2 / NQN_U-2×7 5 NQN_U-2×2 / NFN-12×2 / / NFN-12×2 / NQN_U-2×7

[0107] [Table 2]

[0108] [Table 3]

[0109] [Comparative Examples 1 and 2] A multilayer sheet was produced and evaluated in the same manner as in Example 1, except that the layer structure of the precursor was changed as shown in the table. As shown in Table 3, peeling was not possible in this example. It was suggested that when the amount of particulate inorganic filler in layer FE is large, another layer of a certain thickness is required on the layer.

[0110] The layer structure is shown below. Comparative Example 1 NQN-2 / NFN-11×3 / / NFN-11×3 / NQN_U / NQN_U 2 NQN-2 / NFN-12×3 / / NFN-12×3 / NQN_U / NQN_U

[0111] [Evaluation method] [Total ethylene content of component (A) (component (A1) + component (A2)), ethylene-derived unit content of component (A1)] The copolymer sample dissolved in a mixed solvent of 1,2,4-trichlorobenzene / deuterated benzene / hexamethyldisiloxane = 30 / 10 / 1 (volume ratio) was analyzed by AVANCE III HD400 ( 13 The conditions were: measurement temperature 120°C, flip angle 45°, pulse interval 7 seconds, sample rotation speed 20Hz, and cumulative number 6000. 13 C-NMR spectra were obtained. Using the spectrum obtained above, the total ethylene content (wt%) of component (A) was determined by the method described in Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules, 15, 1150-1152 (1982). When component (A1) is used as a sample for measurement, the total ethylene content (wt%) obtained by the above method is the ethylene unit content (wt%) of component (A1). When component (A1) contains units derived from a comonomer other than ethylene, the content of the comonomer units can be determined in the same manner as the content of the ethylene-derived units.

[0112] [Ethylene unit content in component (A2)] The ethylene unit content (wt%) of component (A2) was calculated in the same manner as for the total ethylene amount, except that the integrated intensity T'ββ calculated by the following formula was used instead of the integrated intensity Tββ calculated when measuring the total ethylene amount of component (A) by the method described in the above document. T'ββ=0.98×Sαγ×A' / (1-0.98×A') Here, A'=Sαγ / (Sαγ+Sαδ), and Sαγ and Sαδ described in the above literature It is calculated as follows. In component (A), which consists of components (A1) and (A2), when component (A1) contains ethylene units, the content of ethylene-derived units in component (A2) was calculated by the following formula when the weight ratio (component (A2) / [component (A1)+component (A2)]) was clear from the polymerization conditions. Content of ethylene-derived units in component (A2) (unit: weight%)= [Total ethylene content of component (A) - Ethylene-derived unit content of component (A1) x Content of component (A1) in component (A)] / (Content of component (A2) in component (A))

[0113] [Weight ratio component (A2) / [component (A1) + component (A2)]] It was calculated using the following formula. Component (A2) / [Component (A1)+Component (A2)](unit: weight %)=total ethylene content of component (A) / (ethylene unit content in component (A2) / 100)

[0114] [Liquidity MFR] The MFR of polypropylene resins was measured by adding 0.05 g of H-BHT manufactured by Honshu Chemical Industry Co., Ltd. to 5 g of sample and homogenizing by dry blending, and then measuring the MFR at a temperature of 230°C and a load of 2.16 kg based on JIS K7210-1 and JIS K6921-2. The MFR of the polypropylene resin composition was measured in accordance with JIS K7210-1 and based on JIS K6921-2 under conditions of a temperature of 230° C. and a load of 2.16 kg.

[0115] [Peeling test] A 180-degree peel test was carried out using an Autocom universal testing machine manufactured by TSE Corporation. The sheet produced in the above example was cut into strips 15 mm wide to prepare test pieces. The top layer and the bottom layer were clamped between the grips. The distance between the grips was 50 mm, and the tensile test was carried out by moving the grips at a speed of 300 mm / min. The specimen was pulled for 100 mm or more, and the average test force in the stable zone of 50 mm during material destruction was used as the test value. When the top layer was a coating, the layer immediately below it was clamped with the gripping tools.

[0116] [Melting point Melting point by DSC (TmF, TmN, TFm out )] Approximately 3 mg of biaxially oriented coextruded sheet-like member C' (NFN-9 to 12) was sampled and weighed on an electronic balance, and then the sample was measured using a differential scanning calorimeter (DSC) (Q-200 manufactured by TA Instruments) by holding the sample at 30°C for 10 minutes, and then heating the sample to 230°C at a heating rate of 10°C / min to obtain a melting curve. The peak temperature (TmF') of the melting curve was determined, and the melting point TmF was determined based on the above formula (i). The melting point TmF of the outermost layer of layer F of precursor 1' of the multilayer sheet was calculated. out The same was also found for. In measuring the melting point TmN, a biaxially oriented polypropylene prepared under the conditions described in [Biaxially oriented sheets NFN-9 to 12] was used as the raw sheet of a single layer of resin composition (k). DSC measurement was performed on this biaxially oriented polypropylene in the same manner as above, and the peak temperature (TmN') of the melting curve was obtained, and the melting point TmN was calculated based on the formula (ii). [Explanation of symbols]

[0117] 10 Easy Peel Layer 15 Adhesive layer 20 Top Tier 30 Other layers 1 Multi-layer sheet F. Filler layer F FE Filler layer FE N NEETs 1' Precursor F' Biaxially oriented polypropylene sheet member FE' Biaxially oriented polypropylene sheet material N' Biaxially oriented polypropylene sheet member f. Resin composition constituting layer F Resin composition constituting the fe layer FE n Resin composition constituting layer N F” Unstretched polypropylene sheet (raw sheet) FE” Unstretched polypropylene sheet (raw sheet) N” Unstretched polypropylene sheet (raw sheet) C' Biaxially stretched coextruded sheet member 2. Unstretched sheet preparation process 3 Stretching process 4 Lamination process 5 Interlayer fusion process PI Polyimide Tape

Claims

1. A polypropylene multi-layer sheet having a thickness of 0.1 to 5 mm, The laminate has alternating layers in which a biaxially oriented polypropylene layer F having a melting point TmF and a biaxially oriented polypropylene layer N having a melting point TmN are alternately laminated, TmF ≧ TmN, the layer F is formed from a resin composition containing a polypropylene-based resin as a component (A) and an inorganic filler as a component (B), and the weight ratio of the component (B) / [component (A)+component (B)] is more than 0 to 60% by weight; the layer N is formed from a resin composition containing a polypropylene-based resin as component (a) and the component (B), the weight ratio of component (B) / [component (a)+component (B)] being 0 to 2% by weight, Meet any of the following requirements: (I) At least one of the layers F is a layer FE in which the component (B) is a particulate inorganic filler and the weight ratio of component (B) / [component (A)+component (B)] is 3% by weight or more and less than 15% by weight, (II) At least one of the layers F is a layer FE in which the component (B) is a granular inorganic filler, and the weight ratio of component (B) / [component (A)+component (B)] is 15 to 35% by weight, and r / R is ≧5%, where r is the shortest distance from the surface of the multilayer sheet in the thickness direction to the interface between the layer FE and another layer, and R is the total thickness of the multilayer sheet. Polypropylene multi-layer sheet.

2. The component (A) is a polypropylene-based resin composed of a component (A1) and an optional component (A2), The component (A1) is 100 to 50% by weight of a propylene (co)polymer containing 0 to 10% by weight of a comonomer-derived unit selected from C2 to C10 α-olefins (excluding C3 α-olefins); Component (A2) is 0 to 50% by weight of an ethylene-α-olefin copolymer containing more than 10% by weight and not more than 90% by weight of units derived from ethylene; The MFR (230°C, load 2.16 kg) of component (A) is 1 to 20 g / 10 min. The polypropylene multilayer sheet according to claim 1.

3. 3. The polypropylene multi-layer sheet of claim 1 or 2, further comprising a top layer over said alternating layers.

4. 3. The polypropylene multilayer sheet according to claim 1, wherein the particulate inorganic filler is calcium carbonate.

5. In the above (I), 30% ≧ r / R ≧ 0.6%, or In the above (II), 30% ≧ r / R ≧ 5%; The polypropylene multilayer sheet according to claim 1 or 2.

6. The polypropylene multilayer sheet according to claim 1 or 2, wherein the layer FE has a thickness of 10 to 1000 μm.

7. A method for producing the polypropylene multilayer sheet according to claim 1 or 2, comprising the steps of: a layer F having a melting point TmF; A step 1 of preparing a precursor in which a layer N having a melting point TmN and a layer F are laminated such that the layers F are not adjacent to each other; a step 2 of contacting an outermost layer of the precursor with a heating body to heat-seal the layers of the sheet; TmF ≧ TmN; Manufacturing method.

8. The melting point of the outermost layer F is defined as TmF out When the temperature T of the heater satisfies the following condition: TmF out -T≧4(℃) (The melting point is measured using a DSC at a temperature rise rate of 10°C / min from 30°C to 230°C.) The method of claim 7.

9. The method of claim 7 further comprising the step of providing a top layer after step 2.

10. A molded article obtained by molding the polypropylene multi-layer sheet according to claim 1.

11. The molded article according to claim 10, which is an automobile part.

12. A polypropylene multi-layer sheet produced by the method of claim 7.

13. The layer FE is used as an easy peel layer; A method for peeling at least one layer from the polypropylene multilayer sheet according to claim 1 or the molded article according to claim 10.

Citation Information

Patent Citations

  • Method for reusing plastic product provided with coating film

    JP1993269743A

  • Method for peeling coating film of resin molding

    JP2007237590A

  • Easily openable laminated film, laminated film and lid material

    JP2008087181A

  • Method for secondary molding of polymer NANO oriented crystal material

    JP2012096526A

  • Polypropylene composition, polypropylene sheet, method for producing polypropylene sheet, and secondarily molded body

    JP2018095698A